Ideational Populism in Chile? A Case Study. Issue 4 (1st September 2017) - Aguilar, Rosario; Carlin, Ryan E.
Abstract: This paper conducts an experimental test of the theory of ideational populism in a most‐likely case: a well‐known Chilean populist presidential candidate, Roxana Miranda. At the time of our study, Chile had the necessary conditions for ideational populism: corruption scandals and a crisis of political representation that lowered citizens' trust in establishment elites. The stimulus was a speech that included the core elements of ideational populist discourse. Despite the careful experimental design and a ripe political atmosphere, we found no effects of populist discourse on voting intentions or evaluations of Miranda among the research participants. We discuss the possible reasons for these null findings. Rather than disqualifying the theory of ideational populism, we conclude that our research calls theorists to incorporate other elements – ideology, gender, issue positions, strategic voting – into their models of ideational populism.